AQUAPONICS: A SUSTAINABLE FOOD PRODUCTION ALTERNATIVE - SREEKUMAR, ASWATHY; PUDHUVAI, BAVEESH; SUNDARAM, PREETHA; DAS, RAJIB (Journal of the Inland Fisheries Society of India, 2024)
A new agricultural production system has to be implemented to meet the food demands of the future global population. Consequently, it is vital to select cropping systems, methods, and technologies based on the agro-climatic characteristics of the region to maximize productivity and produce sustainable output without damaging the environment. Aquaponics is a method that mixes aquaculture with agriculture to produce sustainable quantities of fish and vegetables. This review article explains aquaponics as a system for sustainable food production alternatives, including the evolution of aquaponics, its components, the biotic stresses involved, the designing of aquaponics, the optimum conditions required, deficiency symptoms of plants grown in an aquaponics system, and future aquaponics research requirements. Materials and procedures: A comprehensive and methodical examination of the published publications was performed using Scopus, Web of Science, Google Scholar, and NAAS-indexed journals. Despite having lower nutrient concentrations, aquaponic plants serve nearly as well as hydroponic plants, according to a study of the two approaches. Differences in product quality were observed, as aquaponics provided a more consistent nutrient delivery than hydroponics, according to several research studies. Therefore, aquaponics is a field that necessitates additional research to improve the current setup and sustain global agricultural productivity.